Legal framework for the international transfer of technology. - Liu, Yunhai. (University of Ottawa (Canada), 1992)
The thesis deals with the interaction between the legal controls systems and commercial dimensions of technology transfer. The primary purpose is to undertake a comprehensive examination of the current legal framework which plays an important role in regulating the international transfer of technology. The legal framework for technology transfer is viewed as an overall and integrated concept which consists of major national, regional and international legislation. The focus is upon those which have direct regulatory effects on the proprietary rights over technology, contractual conditions of technology transactions, behaviour of parties concerned, and the inflow and outflow of technology. Emphasis is also consciously placed on the traditional forms of legal regulation in developed countries and on special laws and regulations adopted by developing countries. The main issues are raised and discussed within the context of the North-South relations with respect to international technology transfer. The bilateral and multilateral treaties for the legal protection and legal control of industrial property rights and their transfer are dealt with in an attempt to explore their role and generic characteristics as well as the related issues. The thesis finally examines various aspects of the Draft Code of conduct for the international transfer of technology. The background and the current status of the code negotiations are studied and the outstanding issues are discussed. The Focus is placed upon the disagreement and the conflicting interests between different groups. The legal nature and the future of the Draft code are also observed. The Thesis concluded that the present legal framework is incomplete because of a lack of direct international regulation of technology transactions. The establishment of legally binding rules controlling technology transfer will likely depend upon the future developments in the national and regional legislation and the possible changes to the international political and economic structure.
Keywords: Law.